Analyzing Digital Marketing Strategies of Shopee E-Commerce on Consumer Purchase Decision - Evelyn Aurelia (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study explores how Shopee's digital marketing strategies particularly User-Generated Content (UGC) affect consumer purchase decision-making within the framework of the Theory of Planned Behavior (TPB) and the AIDA model. Using a qualitative approach, the research collected data through in-depth interviews with 18 Shopee users, all of whom had been exposed to various forms of UGC such as reviews, testimonials, Shopee Live content, and social media campaigns. Thematic analysis was employed to extract meaning from 180 user statements, resulting in nine thematic categories aligned with the constructs of TPB (attitude, subjective norms, perceived behavioral control) and AIDA (attention, interest, desire, action). The findings reveal that UGC shapes consumer behavior not merely by influencing attitudes, but by fostering emotional trust, enhancing perceived relevance, and reinforcing community-driven norms. UGC content was found to be particularly effective in attracting attention and guiding users toward action through relatable, visual, and peer-generated narratives. The study underscores the strategic importance of originality, interactivity, and personalization in optimizing UGC effectiveness. This research contributes to a deeper understanding of consumer psychology in e-commerce and offers insights for marketers on leveraging participatory content in digital environments.